The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/09593330.2012.758659
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus removal from aqueous solutions using a synthesized adsorbent prepared from mineralized refuse and sewage sludge

Abstract: Mineralized refuse and sewage sludge generated from solid waste from municipal landfills and sewage treatment plants were sintered as a cost-effective adsorbent for the removal of phosphorus. Compared with the Freundlich model, phosphorus adsorption on the synthesized adsorbent, zeolite and ironstone was best described by the Langmuir model. Based on the Langmuir model, the maximum adsorption capacity of the synthesized adsorbent (9718 mg kg(-1)) was 13.7 and 25.4 times greater than those of zeolite and ironst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…In this case, the sorption capacity of P reached 0.512 mg/g. Our sorption capacity values were mostly in agreement with the values reported in related studies by Chen et al [31] and Jiang et al [32]. Taken together, on the basis of these findings, it can be concluded that straetlingite-based sorbents are suitable for the removal of NH 4 + from aqueous solutions, and especially from wastewater in which P is present.…”
Section: The Sorption Of Nh 4 + Ions By Straetlingite-based Sorbents In Wastewater From An Open Recirculation African Catfish Farming Syssupporting
confidence: 92%
“…In this case, the sorption capacity of P reached 0.512 mg/g. Our sorption capacity values were mostly in agreement with the values reported in related studies by Chen et al [31] and Jiang et al [32]. Taken together, on the basis of these findings, it can be concluded that straetlingite-based sorbents are suitable for the removal of NH 4 + from aqueous solutions, and especially from wastewater in which P is present.…”
Section: The Sorption Of Nh 4 + Ions By Straetlingite-based Sorbents In Wastewater From An Open Recirculation African Catfish Farming Syssupporting
confidence: 92%
“…However, Saltalı et al reported that the optimum NH 4 + -N remove efficiency was achieved at pH 8[31]. A favourable range of pH 4–8 for PO 4 3− -P remove by La/Al-modified zeolite was observed by Meng, while the PO 4 3− -P remove efficiency incresed with the decrease of pH varied from 3.0–10.0[32,33]. The inconsistency in the optimal pH may be attributed to the differences in the chemical compositions of the zeolites tested.…”
Section: Resultsmentioning
confidence: 99%
“…described a decrease of phosphate adsorption capacity from pH 3 to pH 10 when using zeolite as the adsorbent. Some studies on the phosphate adsorption capacity of adsorbents with surface charges like those of zeolite also reported similar phenomena 54 . The removal of phosphate using iron oxide nanoflakes attained the maximum phosphate adsorption efficiency at pH < 6.3 (pH pzc ) 56 .…”
Section: Resultsmentioning
confidence: 65%
“…At pH < pH pzc , zeolite NaP1 and phosphate ions are differently charged. Electrostatic interactions between NaP1 surface and phosphate ions easily occurred, enhancing the adsorption capacity of zeolite 54 . The surface of zeolite NaP1 carried a more negative charge at pH > pH pzc , resulting in a hindered adsorption ability for anions 33,55 …”
Section: Resultsmentioning
confidence: 99%